Study the effect of alcoholic extract raw salvia officnalis on some sex hormones in femle mice white - Razzaq Kbyeh, Frah (Al-Qadisiyah Journal of Pure Science, 2018)
Thirty female mice white used in the experiment for the purpose of knowing the effect of alcoholic extract raw salvia officnalis leaves on the level of sex hormones which were divided animals into three groups experimental rate of ten mice per group dosage group B and C oral daily dose of the extract amount 500 mg / kg of body weight the first group , respectively, in the1000 mg/ Kg of body weight, respectively, either the first set group A treated the same way time and himself as 0.1 ml / g body weight of physiological solution compared to the mindset lasted 30 days dosing was weight when you stop recording the dosage and then kill her blood was collected through a stab heart for the purpose of studies of hormonal (estrogen, progesterone ,luteinizing hormone ,follicle stimulating hormone and prolactin) extract reflected the impact of the variables studied and related to fertility in the following results compared with the control group 1-low body weight was in the doses and the effect of the dose of 1000 mg / kg of body weight was significantly larger dose of 500 mg / kg of body weight at a level significantly 5% P0≤0.05 2 - significant increase in the level of hormones (progesterone, estrogen, luteinizing hormone, follicle-stimulating hormone) in the doses and the effect of the dose of 1000 mg / kg of body weight was significantly larger dose of 500 mg / kg of body weight at a level significantly 5% P0≤0.05 3 - significant decrease in the level of the hormone prolactin in the doses and the effect of the dose of 1000 mg / kg of body weight was significantly larger dose of 500 mg / kg of body weight at a level significantly 5% P0≤0.05